PENGARUH E-PRICE DAN E-TRUST TERHADAP E-LOYALTY PADA ERA PANDEMIK - Wedhana Purba, Ida Bagus Gde Indra; Tirtayani, I Gusti Ayu (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2021)
As time has developed, many e-commerce platforms exist in Indonesia, so that competition in maintaining consumer loyalty on an e-commerce website often occurs. This study aims to determine the effect of e-price and e-trust on e-loyalty and the role of e-trust in mediating it. The research method used is quantitative and using questionnaire. The population used in this study are consumers who have ever shopped online through the Indonesian online marketplace who are domiciled in the province of Bali. The sampling technique in this study was purposive sampling and accidental sampling and a sample of 120 respondents. The data analysis technique used is descriptive analysis and path analysis. The result of this research is that Shopee is e-commerce with the biggest enthusiasts in Bali. E-price and e-trust have a positive and significant effect on e-loyalty, and e-price has a positive and significant effect on e-trust, e-trust can mediate the effect of e-price on e-loyalty. This research is expected to be able to provide input to further researchers, e-commerce providers, sellers who sell in e-commerce, and customers. Providing reasonable prices, security in transactions, trust in online vendors, will certainly increase consumer loyalty, either by not moving to other e-commerce and recommending it to others.